Physiotherapy Management in Cases of Cerebral Palsy Flaccid Ec Microcephaly - Jeara, Orlens Rambu; Naufal, Adnan Faris; Wardani, Rina Kusuma (Universitas Muhammadiyah Surakarta, 2023)
Cerebral Palsy is a disorder of the development of body movement and posture, resulting in movement limitations that can occur starting from the fetus or baby accompanied by disorders of the musculoskeletal system, sensation, perception, awareness, communication, and behavior. the study used a case report study conducted at the Oemah Physiotherapy Clinic in Solo. The cause of cerebral palsy begins during the prenatal period which is caused by infection, anoxia, toxic, genetics, congenital malformations of the brain, the neonatal period occurs due to anoxia, traumatic, and postnatally caused by trauma, infection and toxic. Physiotherapy helps in optimizing children's active movements by using interventions in the form of myofacial release, patterning, and exercise. After being treated for 4 times T1-T4 there was no increase or change in muscle strength by measuring XOTR muscle strength and motor function in children using gross motor function measure (GMFM) and gross motor function classification system (GMFCS) measurements.